PERAN KEUANGAN NEGARA TERHADAP PEMBANGUNAN FOOD ESTATE PADA MASA PANDEMI COVID-19 DALAM MENJAWAB UPAYA KETAHANAN PANGAN DAN KAITANNYA DENGAN ISU LINGKUNGAN - Salshabila Trianggraeni Wandanarum; Asya Tirta Prameswari; Sabrina Elsa Dianti (Politeknik Keuangan Negara STAN, 2021)
Food estate project is a manifestation from Indonesia in order to mitigate food crisis based on FAO warning. This program aimed for food security provokes pros and cons cause of environment impact risks. These impacts may burden state budget (APBN) in the future. Expenditure allocation is reviewed through literature review method to take a look some aspects inside and the urgency of food estate during this pandemic situation. Historical data and previous research are reviewed to understand the implementation of food estate program in the past. Case study of other country is aimed to get wider perspective in sustainable agriculture practice in order to manifest food security in Indonesia. Import dependency ratio of agriculture product, Indonesian staple food, makes food estate becomes urgent, moreover this program has been implemented. Government should give attention to potential and past environmental impact and look for options for sustainable agriculture to mitigate more expenditure in the state budget.